Transforming a global human resource service delivery operating model using Lean Six Sigma - Anna Trubetskaya (SAGE Publishing, 2021)
The purpose of this study is to outline a transformation model that can help commercial enterprises to design, develop and launch a transformation programme of change within its global human resource (HR) operations function using the Six Sigma Define-Measure-Analyse-Design-Verify (DMADV) methodology. A qualitative approach of a single descriptive case study using the Six Sigma DMADV methodology was chosen to develop an iterative strategic roadmap that enables a HR function to transform its current service delivery operating model in line with organisational challenges. The present results indicate that the design of a strategic planning process, transformation programme and roadmap of prioritised improvement initiatives can enable human resource management (HRM) functions to scale their operating model into the future. Furthermore, the flexibility of the DMADV methodology means that the proposed model may be applied in any function outside of HR and indeed may be of interest to private organisations seeking to develop a similar programme of change.